"Офтальмологічний портрет" синдрому недиференційованої дисплазії сполучної тканини у дітей з набутою міопією - Цибульська, Таміла Євгенівна; Завгородня, Наталія Григорівна; Tsybulska, T. Ye.; Zavhorodnia, T. S. (My University, 2021)
Мета. Визначити офтальмологічні критерії СНДСТ у дітей з набутою міопією. It is established, that the main ophthalmological criteria of the visual analyzer, which allow to discriminate in acquired myopia between the presence of undifferentiated connective tissue dysplasia syndrome and its absence with classification thresholds are: the refractive index of the cornea ≤ 41.5 diopters (sensitivity 88%, specificity 90%), depth of the anterior chamber of the eye ≥ 3.88 mm (sensitivity 87%, specificity 78%), corneal diameter ≥ 11.85 mm (sensitivity 90%, specificity 87%). The obtained data can be useful in a comprehensive assessment of ophthalmological manifestations of the syndrome of undifferentiated connective tissue dysplasia, as well as in prediction of the development of myopic refractogenesis and determination of treatment tactics.
«Ophthalmological portrait» of the syndrome of undifferentiated connective tissue dysplasia in children with acquired myopia